UiTMLaw: Global Lecture Series 2023 with the Faculty of Law, Universitas Islam Bandung, Indonesia - UiTM, Faculty of Law (Faculty of Law, 2023)
The Faculty of Law, UiTM, hosted a delegation from the Faculty of Law, Universitas Islam Bandung, Indonesia, in the UiTMLaw Global Lecture Series 2023. The visit witnessed a delegation of 17 lecturers and 23 postgraduate students from the faculty, led by the Rector of the University Islam Bandung, Prof. Dr. H. Edi Setiadi S.H., M.H. and the Dean of the Faculty of Law, University Islam Bandung, Dr. Efik Yusdiansyah S.H. M.H. The Legal Advisor of UiTM, Prof. Dr. Haidar Dziyauddlin, was also present to meet with the esteemed visitors. During the visit, delegations of both faculties discussed establishing stronger academic networks and internationalization efforts as well as focus group discussions on matching grants between the two faculties. Four lecturers from the Faculty of Law, Universitas Islam Bandung, were also invited to deliver lectures on varying topics; Dr. Chepi Ali Finman Z, S.H. M.H. on Sexual Needs of Indonesian Prisoners, Dr. Sri Ratna Suminar S.H., M.H. on Abortion in the Perspective of Indonesian Law, Dr. Dini Dewi Heniarti S.H., M.H. on Military Criminal Justice System in Indonesia and Dr. Ade Mahmud S.H., M.H. on Renewal of Indonesian Criminal Code. The delegation was also brought to visit UiTM's law library, Perpustakaan Tun Abdul Razak 2 (PTAR 2).